Arduino Basic Training: Making a 12C LCD Running Text for Vocational High School Students - Vitri Tundjungsari; Ai Selpia Andita; Alfina Poetri Abdillah; Ivan Febrian Pratama (Communautaire: Journal of Community Service, 2025)
The development of technology in the era of Industry 4.0 demands increased competencies in the fields of the Internet of Things (IoT) and microcontrollers, especially for students in Vocational High Schools (SMK). Limited hardware and laboratory facilities are major obstacles in practical learning processes. Therefore, utilizing simulation platforms such as Wokwi becomes an effective solution to support microcontroller-based learning. This training aims to provide basic knowledge of Arduino usage through a simulation project of creating a running text on an LCD I2C using Wokwi for SMK students. The method applied combines theory and practice with a participatory approach, involving 25 participants from the Computer and Network Engineering (TKJ) and Visual Communication Design (DKV) departments. The evaluation was conducted using pre-tests and post-tests consisting of 10 multiple-choice questions to measure participants' understanding before and after the training. The results show a significant improvement in post-test scores, particularly in understanding basic concepts of IoT, microcontrollers, and Arduino programming practices. These findings prove that Wokwi is an effective simulation tool for enhancing basic microcontroller programming skills among beginners. Thus, this training model can serve as an alternative solution to support practical learning in schools with limited physical equipment.